The Effect of Person Organizational Fit Mediated by Knowledge Sharing and Organizational Citizen Behavior on Innovative Work Behavior in Marketing Employees - Hindun Silalahi*; Muhammad Irfan Nasution (Universitas Syiah Kuala, 2023)
The term